FSSG Scale System in Comparison with GERD Questionnaires in Predicting Endoscopic Findings with Reflux Esophagitis - Restuti Hidayani Saragih; Imelda Rey (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2012)
ABSTRACTBackground:Gastroesophageal reflux diseases(GERD) frequently manifests in varied symptoms other than its classics (heartburn and regurgitation), this variation might hinder its diagnostic effort. Several questionnaires based on symptoms filled by the patients themselves may help in diagnosing GERD without previous endoscopic examination. This study objects to compare endoscopic findings in patients which previously asked to fill the questionnaires (frequency scale for the symptoms of GERD (FSSG)) and GERD questionnaire (GerdQ) in pursuit of reliable and valid instrument to detect GERD before endoscopic approaches. Methods: This study was conducted in cross-sectional design involving 72 patients in Adam Malik Hospital, Medan with symptomps of upper abdominal pain or discomfort with or without heartburn/regurgitation. Subjects were asked to fill both FSSG and GerdQ and underwent endoscopy. Diagnoses made were classified as reflux esophagitis, functional dyspepsia, or other diagnoses. Subsequently we conduct a comparison analysis of both questionnaires’ specificity and accuracy using receiver operator curve (ROC) by analyzing the area below the curve. Results: According to endoscopic findings from 72 subjects, we ascertained the following results: 52.8% gastritis, antral ulcer, and esophageal hiatal hernia, 37.5% functional dyspepsia, and reflux esophagitis in 9.7% cases. GerdQ is concluded to be superior in terms of specificity and accuracy compared with FSSG with the following percentages in terms of sensitivity, specificity, accuracy, and p value, respectively: 100%, 23.1%, 61.5%, 0.318 vs. 100%, 73.8%, 86.9%, 0.001. Conclusion: GerdQ is superior compared to FSSG in diagnosing GERD based on clinical symptoms in daily practice.Keywords: reflux esophagitis, GERD, FSSG, GerdQ, endoscopy, Los Angeles classification, heartburn.